PELA microspheres with encapsulated arginine–chitosan/pBMP-2 nanoparticles induce pBMP-2 controlled-release, transfected osteoblastic progenitor cells, and promoted osteogenic differentiation. (17th February 2017) - Xu, Xiaolong; Qiu, Sujun; Zhang, Yuxian; Yin, Jie; Min, Shaoxiong
Abstract: Repair of the bone injury remains a challenge in clinical practices. Recent progress in tissue engineering and therapeutic gene delivery systems have led to promising new strategies for successful acceleration of bone repair process. The aim of this study was to create a controlled-release system to slowly release the arginine–chitosan/plasmid DNA nanoparticles encoding BMP-2 gene (Arg-CS/pBMP-2 NPs), efficiently transfect osteoblastic progenitor cells, secrete functional BMP-2 protein, and promote osteogenic differentiation. In this study, chitosan was conjugated with arginine to generate arginine–chitosan polymer (Arg-CS) for gene delivery. Mix the Arg-CS with pBMP-2 to condense pBMP-2 into nano-sized particles. In vitro transfection assays demonstrated that the transfection efficiency of Arg-CS/pBMP-2 nanoparticles and the expression level of BMP-2 was obviously exceed control groups. Further, PELA microspheres as the controlled-release carrier for the nanoparticles were used to encapsulate Arg-CS/pBMP-2 NPs. We demonstrated that the Arg-CS/pBMP-2 NPs could slowly release from the PELA microspheres at least for 42 d. During the co-culture with the PELA microspheres, the content of BMP-2 protein secreted by MC3T3-E1 reached the peak at 7 d. After 21d, the secretion of BMP-2 protein still maintain a higher level. The alkaline phosphatase activity, alizarin red staining, and osteogenesis-related gene expression by real-time quantitative PCR analysis all showed the PELA microspheres entrapping with Arg-CS/pBMP-2 NPs can obviously induce the osteogenic differentiation. The results indicated that the Arg-CS is a suitable gene vector which can promote the gene transfection. And the novel PELA microspheres-nanoparticle controlled-release system has potential clinical application in the future after further research.